Indeks Pembangunan Manusia Dan Pengeluaran Masyarakat Kasus: Yogyakarta - Edy Suandi Hamid (Economic Journal of Emerging Markets, 2002)
Many economists have criticized income per capita as an indicator of economic development. UNDP or World Bank proposes an alternative indicator including non-economic aspects. Since 1990, UNDP has introduced Human Development Index (HDI). The HDI consists of four components that are productivity, equity, sustainability and empowerment and become an important indicator of economic development across the world.Recently, Indonesia already published the HDI for province level as well as regency level. In 2001, the publication shows that DIY province is at second rank after DKI Province. It is amazing because per capita income of household is relatively low. There are two factors affecting higher HDI. Although having low income, most of spending of household is allocated to education and health.